Religious Coping in the Islamic Approach as an Effort to Resolve PTSD in Survivors of Natural Disasters - Hizbullah, Kahfi; Sulistyarini, Indahria; Annatagia, Libbie (Universitas Muhammadiyah Surakarta, 2019)
Purpose: As the largest archipelago in the world, Indonesia in addition to having extraordinary natural potential also has the potential for natural disasters. Since long time ago, Indonesia has often experienced natural disasters, namely natural disasters that are classified as large because it took a lot of victims such as the tsunami in Aceh, the eruption of Mount Merapi in Yogyakarta, the earthquake in West Sumatra and so forth. Natural disasters will certainly cause deep sadness to cause problems, one of which is post-traumatic stress disorder, which will arise if not treated from the beginningMethodology: in this paper uses the literature review methodology, which aims to provide an overview of a concept more strongly based on empirical studies conducted Results: Handling PTSD itself can be done one of them by conducting religious coping in an Islamic approach. In some studies, religious coping can reduce or overcome PTSD symptoms. The Islamic approach is used because if you look at the culture of the people who really hold religious values, especially Islam because the majority is Muslim. The Islamic approach in carrying out religious coping aims to build trust in God, be more dedicated in worshiping, applying Islamic religious values in dealing with problems, and building an Islamic environment. Therefore religious coping combined with Islamic values is felt to be suitable for the conditions of the Indonesian people, so that efforts to overcome PTSD in survivors of natural disasters can be even better.